Pengaruh E-commerce dan Modal Usaha Terhadap Kinerja Keuangan UMKM Kota Padang - Lindy Chintya Darma; Dewi Zulvia; Muhammad Rivandi; Anggi Saputra (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2026)
The purpose of this research is to examine the influence of e-commerce and business capital on the financial performance of MSMEs in the packaged culinary sector in Padang City. The variables used include the dependent variable, financial performance (Y), and the independent variables, e-commerce (X1) and business capital (X2). This research uses quantitative methods, collecting data by distributing questionnaires to 65 respondents using purposive sampling techniques. By using instrument tests (validity and reliability), classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression, and hypothesis testing (t-test and F-test) with the help of the SPSS application, the results show that e-commerce has a positive and significant influence on the financial performance of MSMEs, business capital has a positive and significant influence, and simultaneously e-commerce and business capital have a positive and significant influence on the financial performance of MSMEs in the packaged culinary sector in Padang City.